From fields to bytes: the Internet’s impact on China’s green agricultural revolution - Yi, Xin; Wang, Xiaoyu; Jiang, Qi (Frontiers in Sustainable Food Systems, 2025)
This paper explores the impact of the Internet on the green development of agriculture in China. In the context of China’s agricultural development, this paper underscores the mounting significance of the Internet and explores the potential impact of environmental regulations on the relationship between the two. The analysis used a panel data set encompassing 31 Chinese provinces from 2007 to 2020. The empirical study found that the Internet significantly impacts the efficiency of green development in Chinese agriculture. Further analysis reveals that in comparison with central regions, eastern regions are better positioned to benefit from the information dividends of internet development. In addition, internet development exerts a more substantial promotional effect on the efficiency of green agricultural development in regions specializing in staple food production and balanced agriculture, as opposed to those specializing in staple food sales. The study posits that both command-and-control and market-incentive environmental regulations can enhance the promotional effect of internet development on the efficiency of green agricultural development in China. Furthermore, the study demonstrated that the moderating effects of command-and-control and market-incentive environmental regulations exhibit regional heterogeneity. Specifically, command-and-control environmental regulations have a more substantial moderating effect in eastern regions, while market-incentive environmental regulations have a more substantial moderating effect in western regions. Moreover, the moderating effects of environmental regulations vary across agricultural functional zones. The moderating effect of command-and-control environmental regulations is more substantial in eastern regions, while market-incentive environmental regulations have a more significant moderating effect on grain balance. The findings of this study provide valuable insights into the relationship between the Internet and green agricultural development in China. They also offer important implications for policy-makers.